The Correlation Between Perceived Stress Levels and Academic Self-Efficacy Experienced by UPCD Preclinical Students During the COVID-19 Pandemic/Faith Ashley C. Chua and Mikaela Alessandra I. Millan. - Chua, Faith Ashley C.
INTRODUCTION: The COVID–19 pandemic has taken a toll on everyone in all aspects of life: physically, mentally, emotionally, financially, and even academically. For students, this meant having to participate in a drastic shift to an online setting for school. Completing school requirements, studying for exams, and taking online exams in the midst of a global pandemic all pose daunting challenges. Additionally, students’ academic self–efficacy is constantly called into question as juggling chores, requirements, and events is a struggle. Furthermore, added stress may also come from an acquaintance, relative, household member or the student himself or herself being afflicted with COVID–19. All these serve as factors that affect students’ prescription of their self–efficacy and academic self– efficacy in particular.